Determination diabetes mellitus disease markers in tear fluid by photothermal AFM-IR analysis - Kondrakhova, Daria; Unger, Miriam; Stadler, Hartmut; Zakuťanská, Katarína; Tomašovičová, Natália; Tomečková, Vladimíra; Horák, Jakub; Kimákova, Tatiana; Komanický, Vladimír (Nanomedicine, 2025)
The tear fluids from three healthy individuals and three patients with diabetes mellitus were examined using atomic force microscopy-infrared spectroscopy (AFM-IR) and Fourier transform infrared spectroscopy (FTIR). The dried tear samples showed different surface morphologies: the control sample had a dense network of heart-shaped dendrites, while the diabetic sample had fern-shaped dendrites. By using the AFM-IR technique we identified spatial distribution of constituents, indicating how diabetes affects the structural characteristics of dried tears. FTIR showed that the dendritic structures gradually disappeared over time due to glucose-induced lysozyme damage. The tear fluid from diabetes mellitus patients has a higher concentration of glucose, which accelerates the breakdown of lysozyme and, as a result, the quick loss of the dendritic structure. Our study shows that analysis of dry tear fluid can be promising technique for the detection of glycated proteins that reveal long lasting hyperglycemia and diabetes mellitus.
Keywords: Humans; lidé středního věku; mikroskopie atomárních sil; Female; dospělí; lidé; Biomarkers; glukosa; Tear fluid; Diabetes Mellitus; Adult; biologické markery; spektroskopie infračervená s Fourierovou transformací; ženské pohlaví; Male; Middle Aged; Spectroscopy, Fourier Transform Infrared; Glucose; Muramidase; Tears; mužské pohlaví; muramidasa; diabetes mellitus; Diabetes mellitus; slzy; Microscopy, Atomic Force; Photothermal AFM-IR analysis